Pengaruh Cash Holding, Financial Leverage dan Profitabilitas terhadap Income Smoothing: Studi Kasus pada Perusahaan Sub Sektor Farmasi dan Riset Kesehatan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Vita Citra Mulyandini; Ariba Rahma Purnamasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the impact of cash holding, finansial leverage, and profitability on income smoothing. Income smoothing refers to managerial actions that may result in unethical manipulation of financial statements. The research focuses on companies in the pharmaceutical and health research subsectors listed on the Indonesia Stock Exchange (IDX) during the periode from 2019 to 2023. The methodology employed is quantitative, utilizing secondary data obtained from www.idx.co.id. After applying sampling techniques, 10 companies were selected as samples for this study from a population of 13 companies. The analysis results indicate that Cash Holding, Financial Leverage and Profitability do not have a significant effect on income smoothing. These findings suggest that internal factors of the company, such as cash management, capital structure, and profitability, are not always indicators that a company is likely to engage in income smoothing within the context of the pharmaceutical and health research sub sectors.